PENGARUH JENIS BAHAN PENGEMAS DAN LAMA PENYIMPANAN TERHADAP KADAR VITAMIN C DAN SUSUT BERAT CABAI RAWIT (Capsicum frutescens L.) - Sri Wulandari; Yusnida Bey; Kartini Desyani Tindaon (Biogenesis, 2012)
interactions on levels of vitamin C and weight loss of chili (Capsicum frutescens L.), which is performed at the Laboratory of Biology Education and the Laboratory of Soil Science FKIP Faperta UR on November-December 2011. The research design was randomized block design (RGD) factorial with two factors: package varians and time of storage. The package varians consist of plastic, newsprint, and banana leaves, and the time of storage consist of 0 day (control), 3 days, 6 days and 9 days with three replications. The parameters in this reseach are vitamin C levels, weight loss, color and texture of chili. The levels of vitamin C and weight loss were analyzed by ANAVA and then tested by DMRT 5% level, while the observation of color and texture were analyzed descriptively. The results showed that the interaction of a banana leaf package varians and storage of 3 days have the highest levels of vitamin C is 55,17 mg and the interaction of a newsprint package varians and storage of 9 days showed the highest weight loss is 26,32%. Banana leaves package varians have the highest levels of vitamin C 51,16 mg and the lowest weight loss is 5,95%. 3 days storage time have the highest levels of vitamin C 53,12 mg and the lowest weight loss is 7,84%. The conclusion is the interaction of banana leaf package varians and 3 days time storage gives the best quality of color and texture compared to other treatment interactions. Banana leaves are good for package chili. The increasing of time storage will increase the weight loss, decrease the vitamin C level and the color and texture quality of chili.Keywords : Chili, Levels of vitamin C, Package varians, Time of storage, Weight loss